Český botanický výzkum na Svalbardu - Klimešová, J. (Jitka); Prach, K. (Karel) (2012)
Participation of Czech scientists in the ecological research in High Arctic is summarized. Vegetation, under those rather extreme environmental conditions, changes very slowly and even we did not detected any change attributed to ongoing climate change.